ROLE OF RHIZOSPHERE ASSOCIATED BACTERIA IN BIODEGRADATION - Mol. S, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The unrestricted use of the organophosphate insecticide chlorpyrifos in agriculture causes environmental pollution and poses a major threat to the world population. In the present study, bacteria were isolated from the rhizosphere of the chili plant. The bacterial strains have plant growth promoting traits. Among the bacterial strains, eight strains produced ammonia, seven bacteria fixed N2, nine bacteria produced indole-3-acetic acid, and seven bacteria produced siderophore. The bacterial strains produced laccase, lignin peroxidase, dechlorinase, and manganese peroxidase. The isolated bacterial strains, K02, and L4, were grown in a culture medium containing chlorpyrifos and significantly degraded chlorpyrifos. Based on morphology, biochemicals, and 16S rDNA sequencing, these strains were identified as Pseudomonas aeruginosa K02 and Bacillus cereus L4. Chlorpyrifos degradation was performed by co-cultivation of P. aeruginosa and B. cereus. These two bacterial strains were incubated for 72 h at various concentrations, pH values between pH 7.0 and 8.0, and various inoculum concentrations. The selected consortia degraded 98.2±1.1% chlorpyrifos after optimized culture conditions.